Practical urban planning for winter cycling : lessons from a Swedish pilot study - Chapman, David; Larsson, Agneta (Journal of Transport & Health, 2021)
Introduction A detailed understanding of how the weather affects cycling is lacking. Where research has been carried out, the focus has often been on temperate and hotter climates; little research has been carried out regarding cycling in colder climate communities. This study therefore investigated the lived experience of winter-season cycling to provide empirical data for planning winter cycling in cold-climate communities. Methods Between 1 December 2017 and 30 April 2018, the activities of 13 cyclists (eight female and five male, mean age 42 years, age range 11–74 years) in Luleå, Sweden, were surveyed. Methods: Structured questionnaires, individual travel diaries, and recorded data for outdoor temperature, precipitation type, and snow cover were used. Results 1) Cycle level and frequency could be maintained during the winter season; 2) in winter, participants were more likely to use their bicycles for commuting than other activities, 3) electric bicycles helped winter cycling significantly; 4) the quality of the cycling infrastructure is critical to making winter cycling attractive. Conclusion For winter cycling to be successful, town planners need to consider winter cycling as a specific activity with its own design, policy and management requirements. This study has shown that year-round cycling can be achieved in cold-climate communities, with all its attendant potential health benefits. Validerad;2021;Nivå 2;2021-04-13 (alebob); Finansiär: City planning administration at Luleå Municipality